2011
DOI: 10.1108/13665621111128673
|View full text |Cite
|
Sign up to set email alerts
|

Team learning and team composition in nursing

Abstract: Purpose -This study aims to explore team learning activities in nursing teams and to test the effect of team composition on team learning to extend conceptually an initial model of team learning and to examine empirically a new model of ambidextrous team learning in nursing. Design/methodology/approach -Quantitative research utilising exploratory and confirmatory factor analyses, and correlation and multiple regression analyses, were used for empirical validation. Findings -Principal component analyses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Statistics were generated to summarize team learning, team composition, contextual and implementationeffectiveness variables. In congruence with the systems approach to contingency theory, the fit was analysed using correlation and multiple regression analyses [38,39] . Relationships between variables were explored using the Pearson product-moment correlation coefficient [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Statistics were generated to summarize team learning, team composition, contextual and implementationeffectiveness variables. In congruence with the systems approach to contingency theory, the fit was analysed using correlation and multiple regression analyses [38,39] . Relationships between variables were explored using the Pearson product-moment correlation coefficient [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Learning within teams has been seen as particularly important by a number of researchers, including Senge (1990, 10) Zellmer-Bruhn and Gibson 2006), but it is more common to define it in terms of processes (e.g. Boak 2014;Bucic, Robinson, and Ramburuth 2010;Fisser and Browaeys 2010;Gibson and Vermeulen 2003;Savelsbergh, van der Heijden, and Poell 2010;Timmermans et al 2011). For example, Edmondson (2002, 129) defines team learning as 'a process in which a team takes action, obtains and reflects upon feedback, and makes changes to adapt or improve'.…”
Section: Team Learning Action Research and Action Learningmentioning
confidence: 99%
“…Some studies have identified structural factors within the team as supportive of team learning, including member familiarity (He, Butler, and King, 2007), team stability (Edmondson 2003;Timmermans et al 2011) and interpersonal trust between team members (Akgun et al 2013;Gibson and Vermeulen 2003).…”
Section: Team Learning Action Research and Action Learningmentioning
confidence: 99%
“…For example, Fisser and Browaeys (2010), Van den Bossche et al (2006), Van der Vegt andBunderson (2005), Van Offenbeek (2001), Van Woerkom andCroon (2009), Wilson et al (2007) and Timmermans et al (2011) focus on information management, interpretation and dialogue as the core activities of team learning.…”
Section: Team Learning Literaturementioning
confidence: 99%
“…Research settings include surgical teams (Edmondson et al, 2001;Vashdi et al, 2013), the pharmaceutical and medical sector (Gibson and Vermeulen, 2003) teams of college students (Sessa et al, 2011;Van Offenbeeck, 2001) the oil and gas industry (Van der Vegt and Bunderson, 2005) and police and fire services (Boon, 2013). Researchers are, on the whole, interested in influences on work team performance, or more specifically the impact of team learning on team performance, (Chan et al, 2003;Edmondson, 1999;Edmondson, 2002;Savelsbergh et al, 2010;Zellmer-Bruhn and Gibson, 2006).and the factors within the team or in its environment that are conducive to team learning (Boon et al, 2013;Bucic et al, 2010;Edmondson et al, 2001;Timmermans et al, 2011).…”
Section: Team Learning Literaturementioning
confidence: 99%